American Audiences on Movies and Moviegoing - Stempel, Tom (Book collections on Project MUSE., 2015)
A unique perspective on half a century of American cinema -- from the audience's point of view. Tom Stempel goes beyond the comments of professional reviewers, concentrating on the opinions of ordinary people. He traces shifting trends in genre and taste, examining and questioning the power films have in American society. Stempel blends audience response with his own observations and analyzes box office results that identify the movies people actually went to see, not just those praised by the critics. Avoiding statistical summary, he presents the results of a survey on movies and moviegoing i.